Relationship between insulin resistance and muscle triglyceride content in nonobese and obese experimental models of insulin resistance syndrome - Divisová, Jana; Kazdová, Ludmila; Hubová, Miriam; Meschisvili, Ellen (Annals of the New York Academy of Sciences, 2002)
In nonobese hereditary hypertriglyceridemic (HTg) rats and obese HTg Koletsky SHROB/Kol rats, muscle triglyceride accumulation and its relationship to glucose homeostasis and tissue sensitivity to insulin action were examined. Soleus muscle and diaphragm triglyceride contents were markedly increased in HTg rats as compared with controls and were further increased in obese animals. On the other hand, glucose intolerance and impairment of insulin-stimulated in vitro glycogen synthesis were of a similar degree in nonobese as well as obese animals. Results indicate that insulin resistance did not increase proportionally to muscle triglyceride content.
Keywords: Animals; svaly; glukózový toleranční test; triglyceridy; druhová specificita; Obesity; Triglycerides; Glucose Tolerance Test; Species Specificity; obezita; Male; modely nemocí na zvířatech; Insulin Resistance; Disease Models, Animal; inzulinová rezistence; krysa rodu Rattus; Muscles; mužské pohlaví; zvířata; Rats